Experiments to Measure the Sorption Isotherm of Gamma Alumina (γ-Al2O3) - Vu, Hong Thai (Old Journal, 2018)
Gamma Alumina (γ-Al2O3) is a material with many good properties such as small pore size, high specific surface area, highly hygroscopic, low melting temperature, ...These characters are very suitable for making adsorbent and catalyst carriers. Gamma alumina is widely applied in many industries such as petrochemical industry, chemical industry, pharmaceutical industry, ...Study of γ-Al2O3 is very important. One of the most important characters of γ-Al2O3 is the sorption isotherm. This work will present the experimental results to determine the sorption isotherm of γ-Al2O3. Comparison between experimental results and Lanmuir, (Brunauer, Emmett and Teller) BET models is also introduced.